Advisory Opinion 001/2020 on the Right to Participate in the Government of one's Country in the Context of an Election held During a Pandemic such as the COVID-19 Crisis (Afr. Ct. H.P.R.). (August 2022) - Mwangi, Jacquelene
Abstract : One of the many implications of the measures taken to contain the spread of the COVID-19 crisis was the potential limitation of citizens to participate in their governments, namely through free, fair, and transparent elections. Recognizing the risks this would pose to political stability and governmental legitimacy in Africa, the Pan African Lawyers Union (PALU) submitted a Request for an Advisory Opinion to the African Court of Human and Peoples' Rights (the Court) on the right of citizens to participate in the government of their country in the context of an election during the COVID-19 pandemic. The Court's Opinion was that the decision to conduct or postpone elections was a matter of domestic law, but that any such decision had to comply with regional and international standards on restriction and suspension of rights during emergencies.